Makna Komunikasi Keluarga dalam Video Klip Hindia “ Secukupnya” - Rizaldy; O. Hasbiansyah (UNISBA Press, 2022)
Abstract. Hindia video clip entitled “Sufficiently” The video clip uploaded on the Sun Eater youtube channel on May 3, 2019 shows texts that have stories, most of these texts are related to family matters. this video clip has been viewed by 4,954,475 people to date. Therefore, the researcher is interested in researching the meaning of family communication in the Indies Video Clip